Bi-Hamiltonian systems and Lotka-Volterra equations: A three dimensional classification - Manfred Plank (Institute for Advanced Studies (IHS), 1995)
We study three dimensional bi-Hamiltonian systems in general and use the obtained results to classify all three dimensional Lotka-Volterra equations, which admit a bi-Hamiltonian representation. – – In der vorliegenden Arbeit studieren wir drei-dimensionale bi-Hamiltonsche Systeme und klassifizieren alle drei-dimensionalen Lotka-Volterra Gleichungen, welche eine bi-Hamiltonsche Darstellung zulassen.
Keywords: C73; 330; Hamiltonian systems; Lotka-Volterra equations